Analisis Efektivitas Mesin Pneumatic Crimping pada PT. Global Rising Technologies Perkasa - Nuradilah, Nuradilah; Tarigan , Elsya Paskaria Loyda (Fakultas Teknik UMRI, 2025)
PT Global Rising Technologies Perkasa is a contractor engaged in the assembly of high-end wire and cable, as well as box build assembly for the automotive, semi-conductor and medical industries globally. One of the machines used, namely the pneumatic crimping machine, does not operate effectively in its production process. Continuous use of pneumatic crimping machines if not maintained properly causes damage and downtime to the machine. Downtime data that occurred on pneumatic crimping machines from July 2023 to June 2024 was 340 hours. The purpose of this study was to find the factors that cause pneumatic crimping machines to experience high downtime and find ways to reduce it. The analysis method used to measure machine effectiveness is overall equipment effectiveness (OEE), identifying the Six Big Losses using a Pareto diagram, and analyzing the main causes using a Fishbone Diagram. The results of this study show that the average OEE value of pneumatic crimping machines is 67%, far from the international standard of 85%, so it is considered low. The main factors causing high downtime are Equipment Failure Losses of 13% and Idling Minor Stoppages of 22%. There are two pillars of Total Productive Maintenance (TPM) used as a solution, Planned Maintenance and Autonomous Maintenance. With this implementation, the level of operational effectiveness will increase and downtime caused by damage to the pneumatic crimping machine will be reduced.